Neuroprotective effects of microRNA‐211‐5p on chronic stress‐induced neuronal apoptosis and depression‐like behaviours. Issue 14 (13th June 2021) - Shen, Jie; Zhang, Ping; Li, Ye; Fan, Cuiqin; Lan, Tian; Wang, Wenjing; Yu, Shu Yan
Abstract: Findings from recent studies have revealed that microRNAs (miRNAs) are related to numerous neurological disorders. However, whether miRNAs regulate neuronal anomalies involved in the pathogenesis of depression remain unclear. In the present study, we screened miRNA expression profiles in the CA1 hippocampus of a rat model of depression and found that a specific miRNA, microRNA‐211‐5p, was significantly down‐regulated in depressed rats. When miR‐211‐5p was up‐regulated in these rats, neuronal apoptosis within the CA1 area was suppressed, effects which were accompanied with an amelioration of depression‐like behaviours in these rats. These neuroprotective effects of miR‐211‐5p in depressed rats appear to result through suppression of the Dyrk1A/ASK1/JNK signalling pathway within the CA1 area. In further support of this proposal are the findings that knock‐down of miR‐211‐5p within the CA1 area of normal rats activated the Dyrk1A/ASK1/JNK pathway, resulting in the promotion of neuronal apoptosis and display of depression‐like behaviours in these rats. Taken together, these results demonstrate that deficits in miR‐211‐5p contribute to neuronal apoptosis and thus depression‐like behaviours in rats. Therefore, the miR‐211‐5p/Dyrk1A pathway may be critically involved in the pathogenesis of depression and serve as a potential therapeutic target for the treatment of depression.